Enhanced Sub-ppm NH3 Gas Sensing Performance of PANI/TiO2 Nanocomposites at Room Temperature - Zhu, Chonghui; Cheng, Xiaoli; Dong, Xin; Xu, Ying ming (Frontiers in Chemistry, 2018)
PANI/TiO2 nanocomposites spheres were synthesized using a simple and efficient one-step hydrothermal process. The morphology and structure of PANI/TiO2 nanocomposites spheres were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques. The PANI/TiO2 nanocomposite sphere-based sensor exhibits good selectivity, sensitivity (5.4 to 100 ppm), repeatability, long-term stability and low detection limit (0.5 ppm) to ammonia at room temperature (20 ± 5°C). It also shows a good linearity relationship in the range of 0.5–5 and 5–100 ppm. The excellent NH3 sensing performance is mainly due to the formation of the p-n heterostructure in the nanocomposites.